ALWPs Improve Cognitive Function and Regulate Aβ Plaque and Tau Hyperphosphorylation in a Mouse Model of Alzheimer’s Disease - Nam, Youngpyo; Joo, Bitna; Lee, Ju-Young; Han, Kyung-Min; Ryu, Ka-Young; Koh, Young Ho; Kim, Jeongyeon; Koo, Ja Wook; We, Young-Man; Hoe, Hyang-Sook (Frontiers in Molecular Neuroscience, 2019)
Recently, we reported that ALWPs, which we developed by combining Liuwei Dihuang pills (LWPs) with antler, regulates the LPS-induced neuroinflammatory response and rescues LPS-induced short- and long-term memory impairment in wild-type (WT) mice. In the present study, we examined the effects of ALWPs on Alzheimer’s disease (AD) pathology and cognitive function in WT mice as well as 5×FAD mice (a mouse model of AD). Here, we found that administration of ALWPs significantly reduced amyloid plaque levels in 5×FAD mice and significantly decreased amyloid beta (Abeta) levels in amyloid precursor protein (APP)-overexpressing H4 cells. In addition, ALWP administration significantly suppressed tau hyperphosphorylation in 5×FAD mice. Oral administration of ALWPs significantly improved long-term memory in scopolamine (SCO)-injected WT mice and 5×FAD mice by altering dendritic spine density. Importantly, ALWPs promoted spinogenesis in primary hippocampal neurons and WT mice and modulated the dendritic spine number in an extracellular signal-regulated kinase (ERK)-dependent manner. Taken together, our results suggest that ALWPs are a candidate therapeutic drug for AD that can modulate amyloid plaque load, tau phosphorylation, and synaptic/cognitive function.